2021
DOI: 10.1038/s41598-021-93911-4
|View full text |Cite
|
Sign up to set email alerts
|

Anthelmintic resistance and homeostatic plasticity (Brugia malayi)

Abstract: Homeostatic plasticity refers to the capacity of excitable cells to regulate their activity to make compensatory adjustments to long-lasting stimulation. It is found across the spectrum of vertebrate and invertebrate species and is driven by changes in cytosolic calcium; it has not been explored in parasitic nematodes when treated with therapeutic drugs. Here we have studied the adaptation of Brugia malayi to exposure to the anthelmintic, levamisole that activates muscle AChR ion-channels. We found three phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 60 publications
2
15
0
Order By: Relevance
“…In addition, the relative order of response to a panel of agonists was the same for each species. This is consistent with the fact that a response to nicotine in living B. malayi is found and its characteristics are unremarkable [29,42]. An alternative to pharmacology changes could be that fewer receptors were expressed at the surface of oocytes ex vivo.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In addition, the relative order of response to a panel of agonists was the same for each species. This is consistent with the fact that a response to nicotine in living B. malayi is found and its characteristics are unremarkable [29,42]. An alternative to pharmacology changes could be that fewer receptors were expressed at the surface of oocytes ex vivo.…”
Section: Discussionsupporting
confidence: 83%
“…No meaningful difference in the way the N-AChR from different species responded to various agonists, coupled with delayed maximal responses in more derived receptors suggested that a decrease in overall receptor function was likely responsible for the decreased response. The nicotine response of B. malayi in vivo [29,42], the failure to reconstitute a receptor ex vivo , together with a delayed time to maximal response for the species closest to B. malayi suggests a change that affected expression ex vivo specifically. This could be due to an increased dependence one or more members of the network of regulatory accessory proteins that were not included in the cRNA injected into oocytes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These include the clade IIIb nematode, A. suum that encodes an N-AChR substantially similar to that found in the clade V nematode C. elegans [1,24,36]. The genome of the clade IIIc filarial parasite, B. malayi [41], also contains an acr-16 that is expected to encode a functional N-AChR since the worm responds to nicotine (NIC) in vivo with an influx of cations as expected from functional AChRs [29,42]. Perhaps surprisingly, the B. malayi N-AChR failed to reconstitute a functional homomeric receptor ex vivo in the presence of RIC-3.…”
Section: Acr-16 Is Conserved Across Nematodesmentioning
confidence: 94%
“…ACh leads to a slow increase in baseline movement after prolonged exposure (24 and 48 hours), attributable to inefficient penetration of the lipid cuticle [69] (Figure 1C). Treatment with nicotinic compounds (NIC and LEV) leads to an immediate drop in female and male (10 µM and 100 µM) worm motility followed by quick recovery, mediated by fast responding nAChRs [70]. Treatment with compounds associated with muscarinic activity (ATR, ARE, CAR, OXO) elicit a range of subtle-to-large effects on motility.…”
Section: Resultsmentioning
confidence: 99%